REPRESENTASI KECEMASAN MELALUI PENGGUNAAN GELAS DALAM KARYA FRAGILE ANXIOUS: STUDI KONSEPTUAL PENCIPTAAN KOMPOSISI MUSIK MINIMALIS - Mulyadi, Syifa Friscilla Mulyadi; Virgan, Henry Virgan; Widya Febiyanti (Program Studi Pendidikan Musik, 2025)
Mental health issues are increasingly receiving widespread attention across various disciplines, including the field of music. Music serves not only as a medium for entertainment and communication, but also as a means of emotional expression and psychological reflection. This study aims to examine the process of creating a musical work that addresses the theme of anxiety disorders through a creative approach that combines musical and non-musical elements. The method used is Practice-Based Research (PBR), an approach that places artistic practice at the core of the research process, with reference to the creative stages of exploration, improvisation, and formation. The result of this study is a musical work entitled Fragile Anxious, a minimalist musical composition that uses glass as the primary medium for producing sound. The creative process in creating this work involves musical techniques such as adaptation, repetition, phasing, and augmentation to build an emotional atmosphere that represents anxiety. This study demonstrates that a simple sound medium, such as glass, can be musically processed to present complex psychological expressions. Furthermore, this work demonstrates how music can be a reflective medium for mental health issues and contribute to the development of creative discourse in contemporary music. Thus, this research not only contributes to the artistic realm, but also opens up an interdisciplinary space between music and psychology.